The Bridge That Binds Us: Exploring How Self-Forgiveness Can Help People Live a Content Life - Maria Viola Win; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This article aims at exploring the importance self-forgiveness to help people live a content life. Self-forgiveness is a willingness to abandon self-resentment in the face of one’s own mistake while fostering compassion, generosity, and love toward one-self. Self-forgiveness itself is still an underrated topic because there has not been a lot of research into it. This article explores the reason behind the difficulty of self-forgiveness and ways that someone can take to self-forgive. Moreover, we use Conceptual Analysis of Self-Forgiveness, a psychological approach. The finding of this article is in the form of a novella. The novella tells a story using a contemporary fantasy genre, about a girl and a boy, Luci and Von, who are struggling with their past guilt. After spending time together, Luci is able to muster up the courage to apologize which helps her forgive herself and Von also learns the truth about the accident that happened in the past then visits his dead parents’ grave which also helps him forgive himself and move on.Keywords: self-forgiveness, novella, contemporary fantasy